Ultrasound-promoted preparation of polyvinyl ferrocene-based electrodes for selective formate separation: Experimental design and optimization - POLAT, SEVGİ (My University, 2022)
The selective separation of ions is a major technological challenge having far-ranging impacts from product separation in electrochemical production of base chemicals from CO2 to water purification. In recent years, ion -selective electrochemical systems leveraging redox-materials emerged as an attractive platform based on their reversibility and remarkable ion selectivity. In the present study, we present an ultrasound-intensified fabrication process for polyvinyl ferrocene (PVF)-functionalized electrodes in a carbon nanotube (CNT) matrix for selective electro-adsorption of formate ions. To this end, a response surface methodology involving the Box-Behnken design with three effective independent variables, namely, PVF to CNT ratio, sonication duration, and ultrasonic amplitude was applied to reach the maximum formate adsorption efficiency. The fabricated electrodes were characterized using cyclic voltammetry, X-ray diffraction, Raman spectroscopy, and scanning electron micro-scopy (SEM). SEM images revealed that an optimized ultrasonic amplitude and sonication time provided remarkable improvements in electrode morphology. Through a sedimentation study, we qualitatively demon-strate that the main optimized conditions improved PVF/CNT dispersion stability, consequently providing the highest number of active surface sites for adsorption and the highest adsorption efficiency. The highest per-centage of active electrode surface sites and the maximum adsorption efficiency were 97.8 and 90.7% respec-tively at a PVF/CNT ratio of 3, ultrasonication time of one hour, and 50% ultrasonic amplitude.
Keywords: Fizik; Elektromanyetizma, Akustik, Isı Transferi, Klasik Mekanik ve Akışkanlar Dinamiği; Akustik; Kimya; Biyokimya; Alkoloidler; Temel Bilimler; Physics; Electromagnetism, Acoustics, Heat Transfer, Classical Mechanics and Fluid Dynamics; Acoustics; Chemistry; Biochemistry; Alcaloides; Natural Sciences; AKUSTİK; Temel Bilimler (SCI); KİMYA, MULTİDİSİPLİNER; ACOUSTICS; PHYSICS; Natural Sciences (SCI); CHEMISTRY, MULTIDISCIPLINARY; CHEMISTRY; Akustik ve Ultrasonik; Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Acoustics and Ultrasonics; Chemistry (miscellaneous); General Chemistry; Physical Sciences; Electrochemical separations; Ultrasound; Redox electrode; Optimization; Experimental design; CARBON-DIOXIDE; DISPERSION; PAPER; NANOPARTICLES; GENERATION; REDUCTION; NANOTUBES; ANODE